2020
DOI: 10.17951/j.2020.33.3.221-233
|View full text |Cite
|
Sign up to set email alerts
|

Dream Experiences in Alexithymia

Abstract: <p>Aleksytymia jest zaburzeniem, które w sposób znaczny ogranicza możliwość wglądu we własne stany emocjonalne, tym samym powodując brak identyfikowania i zrozumienia informacji płynących z przeżywanych przez jednostkę emocji. Zaburzenie to obejmuje takie obszary deficytowe, jak: niezdolność do werbalizacji emocji, niezdolność do odróżnienia pobudzenia fizjologicznego od emocji, operacyjny styl myślenia oraz ubóstwo życia wyobrażeniowego. Taki sposób funkcjonowania aleksytymików może mieć istotny wpływ n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Alexithymia in combination with long-lasting negative affect and a high level of stress may lead to a number of disorders, including eating disorders, and susceptibility to addiction and mental disorders (Zdankiewicz-Ścigała, 2017). People with alexithymia also exhibit numerous disorders in the experiencing of dreams, the forms of which correspond to the main symptoms of alexithymia (Bauermann et al, 2008; Rohoza & Obrębska, 2020).…”
Section: Alexithymia Stress and Dreamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alexithymia in combination with long-lasting negative affect and a high level of stress may lead to a number of disorders, including eating disorders, and susceptibility to addiction and mental disorders (Zdankiewicz-Ścigała, 2017). People with alexithymia also exhibit numerous disorders in the experiencing of dreams, the forms of which correspond to the main symptoms of alexithymia (Bauermann et al, 2008; Rohoza & Obrębska, 2020).…”
Section: Alexithymia Stress and Dreamsmentioning
confidence: 99%
“…Their characteristics include susceptibility to infections, a risk of hypertension, eating disorders, and a tendency to suffer from addictions and mental disorders (Zdankiewicz-Ścigała, 2017). Researchers have also found that people with alexithymia experience sleep disorders (Nielsen et al, 2011; Rohoza & Obrębska, 2020). Bauermann et al (2008) conducted an interesting study that focused on sleep difficulties and their connection with alexithymia.…”
mentioning
confidence: 99%